2009
DOI: 10.1519/jsc.0b013e318190f9c2
|View full text |Cite
|
Sign up to set email alerts
|

Single-Leg Lateral, Horizontal, and Vertical Jump Assessment: Reliability, Interrelationships, and Ability to Predict Sprint and Change-of-Direction Performance

Abstract: The purposes of this study were to determine the reliability of unilateral vertical, horizontal, and lateral countermovement jump assessments, the interrelationship between these tests, and their usefulness as predictors of sprint (10 m) and change-of-direction (COD) performance for 80 men and women physical education students. Jump performance was assessed on a contact mat and sprint, and COD performances were assessed using timing lights. With regard to the reliability statistics, the largest coefficient of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
166
4
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(214 citation statements)
references
References 32 publications
16
166
4
11
Order By: Relevance
“…Additionally, previous research has observed significant associations between unilateral horizontal jumps to sprint and CODS. 27 However, further research is warranted to support this contention.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous research has observed significant associations between unilateral horizontal jumps to sprint and CODS. 27 However, further research is warranted to support this contention.…”
Section: Discussionmentioning
confidence: 99%
“…However, the abovementioned assessments require expensive equipment which are not readily available to strength and conditioning and rehabilitation practitioners and involve extensive periods of time to collect and analyse data. Alternatively, single leg hops for distance (SLH) are easier to administer and are cost effective, producing highly reliable measures of lower limb triple extension function, [16][17][18] while able to detect asymmetries 12,17 . Furthermore, this assessment can be used in the field as an indirect measure of unilateral lower body horizontal power, force propulsion and acceptance, which can be used to provide rehabilitation and training information.…”
Section: Introductionmentioning
confidence: 99%
“…Strong inverse relationships have been observed between SLH and triple hops for distance (SLTH) with CODS 10,18,22 attributed to the similarities in the force vector and push off mechanism 16 . Conversely, there is a paucity of research investigating the influence of between limb asymmetries from horizontal hops for distance on CODS.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous research has investigated unilateral asymmetry and sought to correlate single leg jumping performance with sprinting and change of direction performance. [8][9][10] Considerably less research has investigated bilateral force production asymmetry and the majority examined previously injured populations. [11][12] Yoshioka et al 20 assessed bilateral strength asymmetry in a computer simulation model, and their results indicated that jump height was not affected by strength asymmetry and that the stronger leg possibly compensated for the weaker leg.…”
Section: Introductionmentioning
confidence: 99%